Learning Ecology: The Dimensions Of Connectedness In Contemporary Arabic Language Pedagogy - Nurcholis, Agung; Zaen, Azhar Amir; Danis, Ahmad Ali Abdullah (Ijaz Arabi Journal of Arabic Learning, 2025)
The ecological approach enables a more holistic understanding of connectedness as an emergent phenomenon arising from interacting various elements in the language learning ecosystem. This article explores the dimensions of connectedness in Arabic language learning through the perspective of learning ecology. Using data from a case study at Pondok Pesantren Darussalam Gontor Ponorogo, Indonesia, this research analyzes how complex interactions between learners, teachers, environment, and language form a dynamic learning ecosystem. Through a mixed methods methodology, the study identifies four main dimensions of connectedness: interpersonal connectedness, contextual connectedness, conceptual connectedness, and spiritual-cultural connectedness. The results show that learning ecosystems rich in connectedness correlate positively with improved Arabic language competence (r = 0.74, p 0.01) and developing a more integrated linguistic identity. This article proposes an "Ecology of Connectedness" model that emphasizes connectedness's dynamic, contextual, and emergent nature in Arabic language learning. This model offers a new theoretical framework to help Arabic language educators design learning environments that facilitate various forms of connectedness and support sustainable language development. The implications of this research extend the understanding of Arabic language learning beyond traditional cognitive-individual approaches toward a perspective that recognizes the central role of connectedness in language learning ecology.